HIDRODINÂMICA DE UM SISTEMA DE ALAGADO CONSTRUÍDO UTILIZADO NO TRATAMENTO DE REJEITO SALINO - SANDAKA, GUILHERME (2018)
Desalination process by ultra filtration and reverse osmosis generates a saline concentrate residue. In order to investigate a possible treatment for this residue and further use for irrigation, a parallel study is being conducted using wetlands. The wetland is built in a 100 L circular shaped tank, in which is established a root zone. The concentrate circulates in this zone creating a hydraulic circuit and a mass transfer zone. The investigation of the flow in this region, the wetland hydraulic evaluation and the hydrodynamic diagnosis of the tank that will be used are the objects of study in this dissertation. This research was conducted using a similar tank to the one that will be used for constructing the wetland. Data from a saline tracer that was released during the flow on this tank were taken in order to a computational processing and further diagnose. Data were obtained from electrical signals from electrodes installed in the circulation tank and using the signal conductivity-concentration correlation, the tools were defined for feeding the computational processing that allowed the results of this work. It was possible to verify the diverse flow characteristics on the flow configurations tested, such as the real detention time, the detection of short-circuit zones, densimetric deposition and the verification of the continuity by the propagated mass. It can be seen in the images obtained in the present work, the densimetric deposition of tracer on the bottom of the tank in all tested configurations. The results allowed to conclude on several aspects to be considered in the forms of operation, as well as in the interferences to be implanted in the zone of roots and in the own methodology used in this system of investigation of hydraulic characteristics and of mass transport.